2007
DOI: 10.1016/j.contraception.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mifepristone on endometrial matrix metalloproteinase expression and leukocyte abundance in new medroxyprogesterone acetate users

Abstract: Objective-The study was conducted to evaluate the effect of Carraguard vaginal gel containing 0.75 mg of levonorgestrel (CARRA/LNG gel) administered in a single dose at different stages of follicle development, over subsequent follicle rupture and hormonal levels.Method-Randomized, blinded, cross-over study comparing the effects of a single administration of CARRA/LNG gel or Carraguard (CARRA) gel. Twenty-four healthy women were enrolled in two centers. The gels were administered when the follicle had reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…It is known that endometrial proliferation depends on oestrogen level, which causes the progressive growth of functional endometrium in the proliferative phase 29 . Flavonoids and triterpenes are components of green tea that move like oestrogen,30, 31, 32, 33 but this study showed no significant result.…”
Section: Discussioncontrasting
confidence: 55%
“…It is known that endometrial proliferation depends on oestrogen level, which causes the progressive growth of functional endometrium in the proliferative phase 29 . Flavonoids and triterpenes are components of green tea that move like oestrogen,30, 31, 32, 33 but this study showed no significant result.…”
Section: Discussioncontrasting
confidence: 55%
“…Results from those studies 110 confirmed good maximum serum LNG levels at 6 and 12 hours following administration. In addition, 114 when women with ovarian follicles of 12–14 mm, 15–17 mm, or ≥18 mm in diameter used either CARRA/LNG or CARRA gel alone, no follicular rupture occurred in the 5-day period following administration in 74% of the CARRA/LNG treatment cycles and in 30% of the CARRA gel cycles. Sexual intercourse did not interfere with the absorption rate of the gel.…”
Section: New Contraceptive Methods Recently Launched In Different Marmentioning
confidence: 92%
“…Treatment of mifepristone significantly downregulated the expression of neuronal nitric oxide synthase (nNOS) and N-methyl-D-aspartate receptor subunit 2B (NR2B) proteins in a rat model of radicular pain [19]. Furthermore, Li et al reported that addition of mifepristone to depot-medroxyprogesterone acetate (DMPA)-exposed endometrium significantly decreased mast tryptase-positive cells and pointed that mifepristone is associated with inhibiting the activity of mast cells [20]. Some studies in China and we also found that mifepristone could be applied in the treatment of adenomyosis.…”
Section: Ivyspringmentioning
confidence: 99%